PENGARUH PENGUMUMAN RIGHT ISSUE TERHADAP KINERJA SAHAM DAN LIKUIDITAS SAHAM DI BURSA EFEK INDONESIA (Sekolah Tinggi Ilmu Ekonomi Atma Bhakti, 2010)
The objectives of this research is to know influence announcement of right issue to stock performance and stock liquidity company in Bursa Efek Indonesia (BEI) at period 2000-2007. This research use technique purposive sampling that obtained sampel counted 55 company. Analysis use statistical examination constructively SPSS program 11.50. In analysing to be used paired sample t test. As well as used one sample statistic to know information content around announcementÂ right. The resultÂ indicates that first, there are difference of stock return mean. Stock return was decline after announcement right issue. Second, there are difference of abnormal return mean Abnormal return was decline after announcement right issue. Third, there are difference of trading volume activity mean. Trading volume activity was increase after announcement right issue